Communication engagements in the planning and implementation of community service among the youth the case of student organization leaders in the University of the Philippines Los Banos - Chico, Mark Lester M. (The Philippine Journal of Development Communication, 2014)
In a dynamic, ever-changing landscape of communication engagements between and among people, the youth is an interesting sector to explore. This study analyzed how student organization leaders in the University of the Philippines Los Banos (UPLB) engaged in communication in the planning and implementation of their community service.